Hambatan Keterwakilan Politik Perempuan Di Indonesia - Wulandari, Lia; Rahmawati, Restu; Rosdiana, Hesti (Prodi Ilmu Politik, 2023)
This study identifies the factors that prevent women in Indonesia from achieving elected office in the provincial level in Indonesia. The results showed that lack of access to financial resources, internal party politics, and women's marital status can be barriers to women achieving elected office. However, access to social and political networks that provide women with key resources, belonging to the dominant religion in your region, and age lead women to greater political success. These findings are based on the interpretation of statistical correlations and content analysis results from in-depth interviews and focus group discussions. The aim of this research is to provide evidence-based findings and recommendations, which can be used to increase the electability of women political candidates in elections.